Speech Act of Prohibition in Minangkabau Language - -, Widya; Agustiana, Erika (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2024)
One sort of speaking behavior that puts the other person's face in danger is prohibiting; therefore, a strategy is needed in saying it so that the interlocutor does not lose face when interacting. The purposes of this study were to characterize the lingual form of speech act of prohibition and the politeness strategies employed in the Minangkabau language to communicate prohibition. The data was taken from the interaction of Minangakabau people who live in Bukittinggi area of West Sumatra. The results demonstrated that prohibiting is realized in three modes of utterances namely declarative, interrogative for indirect speech act of prohibition and imperative form for direct speech act of prohibition. In addition, the politeness strategy used when expressing the speech act of prohibiting consists of bald on records, positive politeness, negative politeness, and off record strategy. It is challenging to conclude that a certain technique is unique to a given context because, in general, the choice of each method depends highly on the utterance's context.